Building a pseudo‐atomic model of the anaphase‐promoting complex. (5th November 2013) - Kulkarni, Kiran; Zhang, Ziguo; Chang, Leifu; Yang, Jing; da Fonseca, Paula C. A.; Barford, David
Abstract : The anaphase‐promoting complex (APC/C) is a large E3 ubiquitin ligase that regulates progression through specific stages of the cell cycle by coordinating the ubiquitin‐dependent degradation of cell‐cycle regulatory proteins. Depending on the species, the active form of the APC/C consists of 14–15 different proteins that assemble into a 20‐subunit complex with a mass of approximately 1.3 MDa. A hybrid approach of single‐particle electron microscopy and protein crystallography of individual APC/C subunits has been applied to generate pseudo‐atomic models of various functional states of the complex. Three approaches for assigning regions of the EM‐derived APC/C density map to specific APC/C subunits are described. This information was used to dock atomic models of APC/C subunits, determined either by protein crystallography or homology modelling, to specific regions of the APC/C EM map, allowing the generation of a pseudo‐atomic model corresponding to 80% of the entire complex.